2015
DOI: 10.1155/2015/579437
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Temperature and Precipitation in the Langat River Basin, Malaysia

Abstract: A study was undertaken to detect long-term trends in the annual and seasonal series of maximum and minimum temperatures. Measurements were taken at 11 meteorological stations located in the Langat River Basin in Malaysia. The rainfall and maximum and minimum temperature data were obtained from the Malaysia Meteorological Department (MMD) and the Department of Irrigation and Drainage (DID) Malaysia. The procedures used included the Mann-Kendall test, the Mann-Kendall rank statistic test, and the Theil-Sen’s slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The increment of TNmean was larger than TXmean, where significant increasing trends were found in each month (0.16-0.6 • C/decade), except February. Comparison of the findings with other Malaysian studies [29,32] confirms the warmer rate of TNmean in Peninsular Malaysia. The annual DTR exhibited a decreasing trend with a rate of 0.07 • C/decade, indicating the differences between TXmean and TNmean are getting smaller.…”
Section: Trend Of Temperature Extremessupporting
confidence: 81%
“…The increment of TNmean was larger than TXmean, where significant increasing trends were found in each month (0.16-0.6 • C/decade), except February. Comparison of the findings with other Malaysian studies [29,32] confirms the warmer rate of TNmean in Peninsular Malaysia. The annual DTR exhibited a decreasing trend with a rate of 0.07 • C/decade, indicating the differences between TXmean and TNmean are getting smaller.…”
Section: Trend Of Temperature Extremessupporting
confidence: 81%
“…Global warming has led to an increase in the climaterelated risks in Malaysia including flood, water stress, agricultural productivity reduction and mosquito-borne infectious disease (Kurane, 2010;Tang, 2019;. Several studies have been conducted to understand the general temperature changes over Malaysia (Amirabadizadeh et al, 2015;Suhaila and Yusop, 2018;Wong et al, 2018). Wai et al (2005) reported increases in the average temperature at annual scale from 0.09 to 0.34 C/decade during the 1971-2001 period.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, studies in dealing with precipitation events and its trends have enormously progressed [3][4][5][6]. On a regional scale, the precipitation trend has decreased in Asia [7,8].…”
Section: Introductionmentioning
confidence: 99%